Pengaruh Pengembangan Karier, Budaya Organisasi dan Beban Kerja terhadap Kepuasan Kerja Karyawan (Literature Review MSDM) - Putri, Ganis Aliefiani Mulya; Fauzi, Achmad; Saputra, Farhan; Danaya, Bayu Putra; Puspitasari, Dita (Jurnal Ekonomi Manajemen Sistem Informasi, 2023)
The aim of this research is to build a hypothesis of the influence between variables which will later be used in further research within the scope of human resource management science. The writing method used in this research is library research, sourced from previous research. Online media used to obtain previous research such as Google Scholar, Publish or Perish, and other academic online media. The results of this research are: 1) Career development influences employee job satisfaction; 2) Organizational culture influences employee job satisfaction; and 3) Workload influences employee job satisfaction.